(untitled) (Medico Legal Update, 2021)
Background: Laryngoscopy and intubation are associated with intensesympathoadrenal stimulation resulting in hypertension, tachycardia & arrhythmias consequent to the release of catecholamines. Various drug regimens and techniques have been used from time to time for attenuating the stress response to laryngoscopy and intubation, including opioids, barbiturates, benzodiazepines, beta blockers, calcium channel blockers, vasodilators etc. Dexmedetomidine is a highly selective alpha 2 receptor agonist having eight times higher affinity and alpha 2 selectivity compared to clonidine and has a shorter duration of action than clonidine. Material and Method: 60 patients scheduled for elective surgical procedures under general anaesthesia belonging to ASA Grade I and II, in the age group of 18 to 60 years were divided into two study groups, D1 and D0.5 received dexmedetomidine 1 µg/kg and 0.5 µg/kg intravenously (iv) over 10 minutes before induction. Hemodynamic responses were compared in both groups by measuring Heart rate (HR),Systolic blood pressure (SBP),Diastolic blood pressure(DBP),Mean arterial pressure (MAP) and SpO2 before giving the test drug (base line values),just before induction,during intubation and at 1 minute, 3 minutes, 5 minutes,10 minutes after intubation. Statistical data were analyzed by using student’s unpaired t test. Observation and Results: Group D1 had 4.70% rise in HR and Group D0.5 had 9.59% rise during intubation which was statistically significant(p<0.05). Maximum rise in SBP and DBP in Group D0.5 was 14.53% and 12.84% respectively, whereas in Group D1 it was 5.55% and 8.90% respectively. In Group D0.5, rise in BP lasted longer after intubation compared to Group D1. Conclusion: The present study demonstrated that ivdexmedetomidine 1µg/kg was better than dexmedetomidine 0.5µg/kg in attenuation of the pressor response of laryngoscopy and intubation without any significant side effects.